Epidemioclinical aspects of breast cancer in women under 35 years at the oncology and palliative care department of Soavinandriana Hospital - Dorland Ranjandriarison, Tafitarilova; Andriamamuhaja, Hanitra Rova Antsafinoana; Livasoa Ralay, Ranaivo; Navoly, Patty; Raparson, Vonjy Harilala; Hasiniatsy, Nomeharisoa Rodrigue Emile (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is rare among women under 35 years, but its incidence is increasing, particularly in low-resource settings. Young patients often present with aggressive disease and delayed diagnosis. This study aimed to describe the epidemioclinical features of breast cancer in this population. Methods: A retrospective descriptive study was conducted from January 2014 to September 2024 at the oncology and palliative care department of Soavinandriana Hospital, Madagascar. 38 women under 35 years old with histologically confirmed breast cancer were included. Results: Among 2,087 breast cancer cases, 38 (1.82%) involved women under 35. The mean age was 30.7 years. Most patients were pauciparous (50%), had breastfed (73.7%), were non-smokers (81.6%), and had no family history of breast or ovarian cancer (76.3%). The upper outer quadrant was the most common tumor site (34.2%). Invasive carcinoma of no special type was predominant (78.9%). Grade II and III tumors accounted for 65.8%. More than 50% of patients were diagnosed at an advanced stage (IIB or higher). Immunohistochemical and staging data were frequently incomplete due to limited diagnostic resources. Conclusions: Breast cancer in young Malagasy women is uncommon but presents aggressively and at advanced stages, underscoring the need for early detection strategies. Improved diagnostic access and tailored screening programs are essential.